Lamp with the Representation of the Griffin: The Christianisation of Pagan Motifs during Late Antiquity - Tešić Radovanović, Danijela T. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The paper deals with the so called griffin lamps. In the group of early Christian bronze lamps, a relatively large number of those with handles in the form of griffin-shaped protome have been preserved. Griffin lamps could be called the prototype of Late Antique production, owing to the manner in which stylistic and iconographic elements of the previous period were combined with the spirit of the age dominated by Christian religion and new Christian aesthetics. The lamps were made in various workshops of the Eastern Mediterranean in the second half of the fourth and fifth centuries. Judging from the total number of preserved copies and variations of the basic type, they enjoyed considerable popularity. Lamp decoration testifies that the Christians during the Late Antiquity period were very receptive to the linking of pagan and Christian motifs, since they did not so easily give up their old patrons and ritual practices.
Keywords: gryphon; griffin; early Christian lamps; Apollo; cross